Hermeneutics as critique : science, politics, race and culture - Simpson, Lorenzo Charles (New directions in critical theory., 2021)
"This book aims to develop the tradition of philosophical hermeneutics, the theoretical account of interpretive (as opposed to explanatory) understanding--the account of meanings and contexts rather than causes and predictions--usually restricted to the domain of literary and textual analysis, in new directions by exploiting its potential as an instrument of critique. It refutes commonly held claims that hermeneutic analyses are necessarily relativistic, Eurocentric, or critically impotent and demonstrates how hermeneutic procedures can inform analyses of urgent current and cross-cultural issues such as the biology of race, female genital excision, and the so-called "culture of poverty" thesis. Lorenzo Simpson demonstrates that a robust methodology of philosophical hermeneutics is well positioned to intervene in critical political and social issues in global ethics and justice in concert with critical theory's emancipatory aims"--